Impact Strategic Green Human Capital, Green Structural Capital, and Green Relational Capital on Financial Performance - Ihsan Nasihin; Dian Purwandari; Hendri Nur Ardiansyah; Desty Prawatiningsih; Erawati Kartika (Eastasouth Institute, 2026)
Study This aim for test influence Green Intellectual Capital (GIC) towards performance finance company with enter size company and leverage as variables control. Study This use approach quantitative with analysis descriptive and multiple linear regression. Secondary data obtained from report annual and reports sustainability company sector energy, materials raw materials and goods non- cyclical consumption listed on the Indonesia Stock Exchange (IDX) during 2019–2024 period. Research result show that Green Intellectual Capital influential positive and significant to performance finance company. In addition, the size company and leverage as variables control participate influence connection the coefficient value determination (R²) shows that the research model capable explain variation performance finance company in a way adequate.